Aplikasi Sistem Imformasi geografis (SIG) Untuk Pemetaan Pola Aliran Air Tanah Di Kawasan Sukajadi Pekanbaru - M Fadhil Nur; Sigit Sutikno; Bambang Sujatmoko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Subdistrict of Sukajadi is one of populous subdistrict in Pekanbaru. Most of the resident use ground water as raw material to supporting necessaries of live everyday because water availability of PDAM is not yet good and less gratify . So that need an effort to taking care of availibility of resource irrigate with have monitoring system of ground water use which can be visualizinged in spasial data and its attribute. This research is intended to know the ground water flow model and availability potency of ground water in Sukajadi subdistrict area of Pekanbaru by using GIS (Geographic Information System). Measurement surveys were conducted twice with condition difference of rainfall, rain duration and sum up the dot measure. Its are measuring ground water surface elevastion of resident well therewith location co-ordinate. The results of data processing by computer base on GIS is contour mapping of ground water surface elevation by interpolation process using Spline method. Depiction of the ground water flow model in Sukajadi subdistrict area of Pekanbaru are conducted by drawing diametrical plump line with contour of ground water surface elevation. Generally stream lines of ground water are resulted moving to go to out of the system (Subdistrict of Sukajadi). Availability of ground water in this research location is depended to input from rainwater and recharge area remained.  Keyword : GIS, Spline, Stream lines of ground water, Availability of ground water